Future-Ready Minds, Resilient Hearts: Understanding Psychological Well-being and Resilience in College Teaching in the Philippines - Durano, April Liza; Banuag, Abelardo; Bate, Lalaine; Dejan, Genesis; Misa, Marie Bless; Paragados, Genesa; Jumao-as, Alberto Jr; Acut, Dharel (Journal of Psychology and Behavior Studies, 2025)
The psychological well-being of college instructors is a critical factor in their professional satisfaction and effectiveness, yet there is limited research on how various dimensions of well-being evolve in response to career challenges and institutional support, particularly for instructors balancing both teaching and administrative duties. This study addresses this gap by exploring the psychological well-being of 12 college instructors in a qualitative case study. Using in-depth interviews, the study examines five key constructs of well-being: emotional, social, professional, physical, and personal well-being. The findings reveal that instructors' well-being is shaped by external pressures, such as the dual demands of teaching and administrative responsibilities, as well as institutional support. Internal factors, including coping strategies, personal reflection, and social support, also play a significant role. Notably, the study identifies the importance of a sense of purpose, work-life balance, and supportive relationships in maintaining resilience against stress. In conclusion, the study emphasizes that a holistic approach to teacher well-being, considering both professional and personal dimensions, is essential for enhancing mental health and job satisfaction. The research underscores the need for institutions to develop tailored, comprehensive well-being programs and suggests that future research should examine the long-term effects of such interventions, particularly for instructors with dual roles, and explore how different teaching contexts influence well-being outcomes.